A study on legal recognition of building surveyor in Malaysia / Muhammad Fikri Othman…[et al.] - Othman, Muhammad Fikri; Shobri, Muhammad Akmal; Mohamed, Aftal Mariz; Abdul Latiff, Nur Fathia (2011)
On 30th March 2011, a local television, TV3 showed a program 'Aduan Rakyaf. This time, the episode is touched on the issue of recognition of the building surveyor in Malaysia. Their stories are also told in the local newspaper, cBerita Harian' which commenced on the issue. They also have extensive coverage by other mass media and electronics. However, their future cannot be determined by them, because without the Building Surveyor Act, there is nothing that can be done in determining their own future in building surveying. For instance, in order for the building surveyor to do their job efficiently and accurately, they must be recognised and hence, the establishment of the Act is very important. Therefore, the project paper is to analyse the effect of interference by Architect in the process of construction and maintenance of the building and to identify the loopholes in the Architect Act 1967, and provide suggestions to improve the situation because currently, there is no Act which protect the work done by the building surveyor of Malaysia. Other than that, this research also aims to propose the recognition of the profession by Government for Building Surveyor in Malaysia.